Hubungan Dukungan Orang Tua dengan Motivasi Belajar Siswa pada Masa Pandemi Covid-19 di Sekolah Menengah Pertama - Nuraini, Sintan Desi; Murtiningsih, Murtiningsih; Inayah, Iin (Yayasan Mandar Indonesia, 2023)
Learning motivations is a sense of enthusiasm felt by students with the characteristics of feeling and taking action to achieve a goal. The role of parents at home greatly influences the student’s learning process during distance learning during the Covid-19 pandemic. The purpose of this study was to determine the relationship between parental support and student learning motivation during the Covid-19 pandemic in junior high schools. This type of research is quantitative with a correlative research design using design cross sectional, using a proportional random sampling technique to 100 respondents. The results of the study were respondents who had high parental support with a high level of learning motivation (65.2%), and with low learning motivation (34.8%). Meanwhile, respondents who have low parental support with a high level of motivation to learn (22,2%), and with low motivation (77,8%) with a value of p = 0.000 (p< 0,05). The results showed a positive relationship between parental support and student motivation in junior high schools. Suggestions for parents are expected to spend their time and pay more attention to children's learning, so that children will have enthusiasm for learning.